Mitochondrial Dysfunction in Stem Cell Aging - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2015)
BACKGROUND: Regardless of the precise underlying molecular mechanisms, the fundamental defining manifestation of aging is an overall decline in the functional capacity of various organs to maintain baseline tissue homeostasis and to respond adequately to physiological needs under stress. There is an increasingly urgent need for a more complete understanding of the molecular pathways and biological processes underlying aging and age-related disorders.CONTENT: Mitochondria constitute the most prominent source of adenosine triphosphate (ATP) and are implicated in multiple anabolic and catabolic circuitries. In addition, mitochondria coordinate cell-wide stress responses and control non-apoptotic cell death routines. The involvement of mitochondria in both vital and lethal processes is crucial for both embryonic and postembryonic development, as well as for the maintenance of adult tissue homeostasis. Age-associated telomere damage, diminution of telomere ‘capping’ function and associated p53 activation have emerged as prime instigators of a functional decline of tissue stem cells and of mitochondrial dysfunction that adversely affect renewal and bioenergetic support in diverse tissues. Constructing a model of how telomeres, stem cells and mitochondria interact with key molecules governing genome integrity, ‘stemness’ and metabolism provides a framework for how diverse factors contribute to aging and age-related disorders.SUMMARY: Cellular senescence defined as an irreversible proliferation arrest promotes age-related decline in mammalian tissue homeostasis. The aging of tissue-specific stem cell and progenitor cell compartments is believed to be central to the decline of tissue and organ integrity and function in the elderly. Taken into consideration that the overwhelming majority of intracellular reactive oxygen species (ROS) are of mitochondrial origin, it is reasonable to posit that the elevated ROS production might be caused by alteration in mitochondrial function during senescence. It is likely that mitochondria and stem cells will remain at the forefront of aging research also for the next decade.KEYWORDS: aging, stem cell, mitochondrial biogenesis, mitophagy, senescence, telomeres